Pengaruh Penambahan Graphene Oxide Terhadap Sifat Bioplastik Berbasis Sagu - Rifati Hanifa; Amun Amri; Syelvia Putri Utami (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Bioplastics are an alternative for conventional plastics that are biodegradable because it can be made from natural materials that can be decomposed by the environment. Bioplastics can be made from sago starch and filler of graphene oxide because its availability and it can improve the mechanical properties of bioplastics. This study aims to make bioplastic from sago starch with the addition of graphene oxide while studying the effect of adding graphene oxide and stirring time for bioplastic mechanical properties. The making of bioplastic was performed by using solution intercalation method while the graphene oxide was synthesized by using Hummers modification method and it produced the dispersed of graphene oxide in the solution. The analyzes were graphene oxide crystallization test, mechanical properties test (elongation and modulus young), morphological test, functional group qualitative test of bioplastic composite and graphene oxid and bioplastic biodegrability. The result of bioplastic tensile strength analysis showed that the addition of graphene oxide and stirring time influenced the bioplastic mechanical properties where the highest tensile strength was 4.018 Mpa for 15% graphene oxide with 50 minute and bioplastic can be naturally degraded 70-80% within 8 days with the highest hydrophobicity of 88.7%. Bioplastic morphological analyzes have shown that 50 minutes stirring time has evenly distributed the filler.Keywords: bioplastic, graphene oxide, hummers, solution intercalation, sago starch.